FACTORS AFFECTING FINANCIAL DISTRESS AND FIRM VALUE IN BANKING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE 2017-2021 - Panjaitan, Harry Patuan; Anraini, Wenfi; Yani, Fitri; Susanti, Roza Sri (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
This research aims to determine the effect of institutional ownership, managerial ownership, current ratio and return on assets on financial distress and its effect on company value in banking companies listed on the IDX for the 2017-2021 period. This study used secondary data. The sample technique in this study used purposive sampling. The number of samples obtained was 25 companies. This research analysis method uses descriptive analysis and several types of evaluation using the help of SmartPLS software. From this study, it was concluded that there is a significant influence between institutional ownership of financial distress and managerial ownership, ROA and financial distress on company value. Managerial ownership, CR, ROA of financial distress as well as institutional ownership and CR of company value have an insignificant influence. Penelitian ini bertujuan untuk mengetahui pengaruh kepemilikan institusional, kepemilikan manajerial, current ratio dan return on asset terhadap financial distress serta pengaruhnya terhadap nilai perusahaan pada perusahaan perbankan yang terdaftar di BEI periode 2017-2021. Penelitian ini menggunakan data sekunder. Teknik sampel pada penelitian ini menggunakan purposive sampling. Jumlah sampel yang diperoleh sebanyak 25 perusahaan. Metode analisis penelitian ini menggunakan analisis deskriptif serta beberapa jenis evaluasi dengan menggunakan bantuan software SmartPLS. Dari penelitian ini diperoleh kesimpulan bahwa adanya pengaruh signifikan antara kepemilikan institusional terhadap financial distress serta kepemilikan manajerial, ROA dan financial distress terhadap nilai perusahaan. Kepemilikan manajerial, CR, ROA terhadap financial distress serta kepemilikan institusional dan CR terhadap nilai perusahaan memiliki pengaruh yang tidak signifikan.